Local-Social Wisdom in the Nyadran Tradition as a Means of Gathering - Toni Julianto; Risky Setiawan; Rufer Firma Harianja (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
Since ancient times the Javanese people have been familiar with the belief system. Before Islam came the beliefs of Animism and dynamism as well as Hindu and Buddhist religions had already developed in Javanese society. Islam is accepted in Javanese society with youth and peace, because preachers have a high tolerance for Javanese culture. One of the forms of cultural acculturation or inherent in the soul of Javanese society is the Nyadran tradition. The Nyadran tradition is a symbolic ritual that is full of meaning Nyadran traditional ceremony includes partially oral folklore because in it there is a form of oral fochlor, namely the prayers used in the ceremony and there is also a form of non-verbal folklore in the form of uba rampe in the ceremony. In socio-cultural terms, the implementation of nyadran tardisi is not only limited to ceremonial cleaning of ancestral burials , salvation (kenduri), making apem cakes, compote, sticky rice, and various snacks from the market which are used as elements of "offerings" as well as being a prerequisite for the ritual prayer procession. However, the nyadran ritual in a socio-cultural context has also become a medium of friendship between families and communities, as well as a social, cultural and religious transformation. Nyadran is an expression and expression of social piety in a society where a sense of mutual cooperation, solidarity, and togetherness is the main pattern of this tradition.